2016
DOI: 10.1080/14786419.2016.1201668
|View full text |Cite
|
Sign up to set email alerts
|

Secondary metabolites from marine-derived Streptomyces antibioticus strain H74-21

Abstract: A new secondary metabolite, (2S,3R)-l-threonine, N-[3-(formylamino)-2-hydroxybenzoyl]-ethyl ester (streptomyceamide C, 1), together with four known compounds 1, 4-dimethyl-3-isopropyl-2,5-piperidinedione (2), cyclo-((S)-Pro-8- hydroxy-(R)-Ile (3), cyclo-((S)-Pro-(R)-Leu (4), and seco-((S)-Pro-(R)-Val) (5), were isolated from the EtOH extract of the fermented mycelium of the marine-derived streptomycete strain H74-21, which was isolated from sea sediment in a mangrove site. The structure of the new compound was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Furthermore, at least 84 new compounds including some “hot molecules,” such as salinosporamides, xiamycins and novel indolocarbazoles, were discovered from mangrove actinobacteria. ( Kyeremeh et al, 2014 ; Xu et al, 2014 ; Ding et al, 2015 ; Fu et al, 2016 ; Han et al, 2016 ; Mangamuri et al, 2016a , b ; Chen et al, 2017 ; Ye et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, at least 84 new compounds including some “hot molecules,” such as salinosporamides, xiamycins and novel indolocarbazoles, were discovered from mangrove actinobacteria. ( Kyeremeh et al, 2014 ; Xu et al, 2014 ; Ding et al, 2015 ; Fu et al, 2016 ; Han et al, 2016 ; Mangamuri et al, 2016a , b ; Chen et al, 2017 ; Ye et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we calculated the configurations between C-7/C-7′, C-8/C-8′ with the lowest energy of compound 1 in ChemDraw [ 16 ]. All of these results suggested that the substitution of the THF ring of 1 should possess a 7, 8- trans /8, 8′- trans /7′, 8′- trans relative configuration [ 17 , 18 , 19 ].…”
Section: Results and Explanationmentioning
confidence: 99%
“…A polycyclic tetramate macrolactam, 16-hydroxymaltophilin (57), isolated from Actinoalloteichus cyanogriseus WH1-2216-6, shows cytotoxicity toward BXPC-3, HCT-116, Jurkat, PANC-1, A549, MCF-7 and L-02 cell lines, with IC 50 values of 4.5, 5.7, 7.5, 7.9, 9.5, 9.7 and 235.9 μM, respectively [38].…”
Section: Macrolides (Lactones) Lactams and α/γ-Pyronesmentioning
confidence: 99%
“…Compound 91 exhibits inhibitory activity toward HCC366, A549 and HCC44 cells, with IC 50 values of 2.8, 4.1 and 8.4 μM, respectively, and compound 92 inhibits HCC366 and A549 cells, with IC 50 values of 2.2 and 3.7 μM, respectively. The compound (2S,3R)-L-threonine, N-[3-(formylamino)-2-hydroxybenzoyl]-ethyl ester (streptomyceamide C, 93) has been isolated from EtOH extract of the fermented mycelium of the marinederived streptomycete strain H74-21 isolated from a sea sediment in a mangrove site [57]. Compound 93 shows cytotoxicity toward MCF-7, with an IC 50 of 27.0 μg/mL.…”
Section: Benzoquinones Naphthoquinones Anthraquinones and Other Aroma...mentioning
confidence: 99%